Evaluation of feline uterine and umbilical arteries blood flow in a pharmacologically induced abnormal gestation model - Blanco, Paula Graciela (2016)
The aim of this study was to describe resistance index (RI) and systolic/diastolic ratio (S/D ratio) of uterine and umbilical arteries in an experimental model of abnormal feline pregnancy pharmacologically induced. On Day 30 to 35 (32 ± 2.9) after mating, twenty domestic short-hair pregnant queens were randomly assigned to one of the following treatment groups: a treated group (TG; n = 8), which received 10 mg/kg of aglepristone SC twice, 24 h apart and a control non-treated group (CG; n = 12). M-Mode and Doppler ultrasonographic evaluations were performed at the initiation of the treatment (Day 0) and then every other day during 8 days (i.e. Days 32, 34, 36, 38 and 40 of gestation) para mi esto no va x q x ej para q empeiza el d 35 estarian mal los dias??. In both groups, uterine and umbilical arteries were evaluated by Doppler ultrasound while fetal heart rate (FHR) was assessed by M-Mode ultrasound. Resistance index of uterine artery augmented in TG from Day 2 onwards, conversely it decreased in CG (P< 0.01). On Day 8, RI values were 0.64 ± 0.05 vs. 0.37 ± 0.01 for TG and CG, respectively. Additionally, S/D ratio of the same artery presented an increase in TG, while this ratio diminished in CG (P< 0.01). On Day 8, this parameter showed values of 2.98 ± 0.4 vs. 1.62 ± 0.06 for TG and CG, respectively. Resistance index of umbilical artery remained almost unchanged in TG from Day 6 onwards, while it progressively decreased in CG throughout the course of the study (P< 0.05). On Day 8, RI were 0.89 ± 0.04 and 0.82 ± 0.01, for TG and CG, respectively. Furthermore on Day 8, S/D ratio of umbilical artery progressively diminished in CG but not in TG (P< 0.01), being 14.7 ± 9.1 vs. 5.9 ± 0.3 for TG and CG, respectively. Fetal heart rate was higher in TG than in CG (P< 0.05). Group differences in Doppler parameters appeared as early as 48 hours after abortion treatment, when the other clinical or ultrasonographic signs were still absent. It is concluded that uterine and umbilical arteries blood flow differed between these normal and induced abnormal cat gestations predicting an adverse obstetric outcome.